Inequality aversion and risk attitudes - Ada Ferrer-i-Carbonell; Xavier Ramos (Institute for the Study of Labor (IZA), 2010)
Using self reported measures of life satisfaction and risk attitudes, we empirically test whether there is a relationship between individuals inequality and risk aversion. The empirical analysis uses the German SOEP household panel for the years 1997 to 2007 to conclude that the negative effect of inequality measured by the sample gini coefficient by year and federal state is larger for those individuals who report to be less willing to take risks. Nevertheless, the empirical results suggest that even though inequality and risk aversion are related, they are not the same thing. The paper shows that the relationship between risk attitudes and inequality aversion survives the inclusion of individual characteristics (i.e. income, education, and gender) that may be correlated with both risk attitudes and inequality aversion.
Keywords: D3; D63; I31; 330; Happiness; inequality aversion; risk attitudes; well-being; Lebenszufriedenheit; Soziale Ungleichheit; Risikopräferenz; Schätzung; Deutschland